Development of language and arithmetic skills: risk and protective factors. Comparative cross-sectional study - Zuanetti, Patrícia Aparecida; Avezum, Marina Dias Macedo de Melo; Ferretti, Marita Iannazzo; Pontes-Fernandes, Angela Cristina; Nune, Marina Estima Neiva; Liporaci, Nelson Macedo; Fukuda, Marisa Tomoe Hebihara; Hamad, Ana Paula Andrade (São Paulo Medical Journal, 2021)
BACKGROUND: In a literate society, linguistic/arithmetic performance is highly valued. Based on defined risk factors, strategies for promotion of better performance can be developed. OBJECTIVE: To ascertain the risk and protective factors relating to development of language and arithmetic. DESIGN AND SETTING: Observational comparative cross-sectional study at a public elementary school in Ribeirão Preto (SP), Brazil. METHODS: A total of 66 children (41% females) attending first to fifth grades participated in this study. They were divided into two groups: G1, children classified as presenting language or arithmetic deficits; G2, average performance. Language (oral and written) and arithmetic skills were assessed through stan- dardized tests. Variables relating to social skills, home environment resources and behavioral problems were assessed through standardized scales. Data on other variables (pre, peri and postnatal complications, maternal variables and others) were collected through interviews. The logistic regression technique with LASSO was used (α = 0.05). RESULTS: Teenage pregnancy and consumption of psychoactive substances during pregnancy or complications during pregnancy were risk factors for performance regarding arithmetic and language. Higher schooling level for the mother was a protective factor in the development of arithmetic and language. Being female and having a history of otitis were risk factors for language. Altered social skills (responsibility and civility) and complaints of inattention were risk factor for arithmetic. Adequate linguistic development was a protective factor for the development of arithmetic. CONCLUSION: The risk/protective factors included variables relating to the gestational period, mother’s age when pregnant, mother’s schooling, social skills, behavior and development issues.